Characterizing the Dyes of Pre-Columbian Andean Textiles: Comparison of Ambient Ionization Mass Spectrometry and HPLC-DAD - Jennifer Campos Ayala; Samantha Mahan; Brenan Wilson; Kay Antúnez de Mayolo; Kathryn Jakes; Renée Stein; Ruth Ann Armitage (Heritage, 2021)
The complex and colorful textiles of ancient Peru have long been a focus of technical study, particularly to characterize the sources of the wide variety of dyes utilized by these Andean artisans. This manuscript describes the characterization of the dyes of both primary (red, blue, and yellow) and secondary (purple, orange, and green) colors sampled from textiles spanning five major civilizations: the Paracas Necropolis, the Nazca, the Wari, the Chancay, and the Lambayeque, all from Peru. All but the Paracas Necropolis samples were part of technical conservation studies of the ancient South American textiles collections of the Michael C. Carlos Museum. Analysis of the dyes was carried out utilizing direct analysis in real time time-of-flight mass spectrometry (DART-MS) and paper spray MS. To validate these ambient ionization MS methods, the samples were further investigated using high-performance liquid chromatography (HPLC) with ultraviolet-visible diode array detection (DAD). These results show that ambient ionization MS methods are simple and fast for characterization of the general classes of dyes, e.g., plant reds vs. insect reds, and indigoids in blues and greens. Due to the myriad possible sources of yellow dyes and their tendency to undergo oxidative decomposition, positively identifying those components in these yarns was difficult, though some marker compounds and flavonoid decomposition products were readily identified by ambient ionization mass spectrometry.